Molecular Taxonomic Profiling of Bacterial Communities in a Gilthead Seabream (Sparus aurata) Hatchery - Califano, Gianmaria; Castanho, Sara; Soares, Florbela; Ribeiro, Laura; Cox, Cymon J.; Mata, Leonardo; Costa, Rodrigo (Frontiers in Microbiology, 2017)
As wild fish stocks decline worldwide, land-based fish rearing is likely to be of increasing relevance to feeding future human generations. Little is known about the structure and role of microbial communities in fish aquaculture, particularly at larval developmental stages where the fish microbiome develops and host animals are most susceptible to disease. We employed next-generation sequencing of 16S rRNA gene reads amplified from total community DNA to reveal the structure of bacterial communities in a gilthead seabream (Sparus aurata) larviculture system. Early- (2 days after hatching) and late-stage (34 days after hatching) fish larvae presented remarkably divergent bacterial consortia, with the genera Pseudoalteromonas, Marinomonas , Acinetobacter and Acidocella (besides several unclassified Alphaproteobacteria) dominating the former, and Actinobacillus, Streptococcus, Massilia, Paracoccus and Pseudomonas being prevalent in the latter. A significant reduction in rearing-water bacterial diversity was observed during the larviculture trial, characterized by higher abundance of the Cryomorphaceae family (Bacteroidetes), known to populate microniches with high organic load, in late-stage rearing water in comparison with early-stage rearing-water. Furthermore, we observed the recruitment, into host tissues, of several bacterial phylotypes - including putative pathogens as well as mutualists - that were detected at negligible densities in rearing-water or in the live feed (i.e. rotifers and artemia). These results suggest that, besides host-driven selective forces, both the live feed and the surrounding rearing environment contribute to shaping the microbiome of farmed gilthead sea-bream larvae, and that a differential establishment of host-associated bacteria takes place during larval development.